2021
DOI: 10.1101/2021.05.11.443570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent loss of chemoreceptors across independent origins of slave-making in ants

Abstract: The evolution of an obligate parasitic lifestyle often leads to the reduction of morphological and physiological traits, which may be accompanied by loss of genes and functions. Slave-maker ants are social parasites that exploit the work force of closely related ant species for social behaviours such as brood care and foraging. Recent divergence between these social parasites and their hosts enables comparative studies of gene family evolution. We sequenced the genomes of eight ant species, representing three … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…While these were published too recently to be included in our in-depth comparative analyses, it is worth noting some striking similarities and differences in these ant groups relative to E. burchellii. Specifically, both studies found large contractions in the OR family in social parasites compared with their free-living relatives (Schrader et al, 2021, Jongepier et al, 2021. This suggests that olfactory system simplification is a common theme of ecological specialization in ants.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…While these were published too recently to be included in our in-depth comparative analyses, it is worth noting some striking similarities and differences in these ant groups relative to E. burchellii. Specifically, both studies found large contractions in the OR family in social parasites compared with their free-living relatives (Schrader et al, 2021, Jongepier et al, 2021. This suggests that olfactory system simplification is a common theme of ecological specialization in ants.…”
Section: Discussionmentioning
confidence: 90%
“…burchellii . Specifically, both studies found large contractions in the OR family in social parasites compared with their free‐living relatives (Schrader et al, 2021 , Jongepier et al, 2021 ). This suggests that olfactory system simplification is a common theme of ecological specialization in ants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, the quality of the reads was assessed using FastQC (Andrews, 2010). Filtered reads were mapped against the T. nylanderi genome assembly (Jongepier et al, 2022) using HISAT2 v2.1.0 (Kim et al, 2015) with the --dta parameter in preparation for genome-guided assembly. The resulting BAM files were sorted and indexed using Samtools v0.1.19 (Li et al, 2009) and used to generate a genome-guided transcriptome assembly using StringTie v1.3.6 (Pertea et al, 2015).…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%